Direct cytogenetic study of chorionic samples of the arrested pregnancy tissues according to the Regional Reproductive Center materials - N. V. Avramenko; D. Ye. Barkovsky; I. V. Semenenko; N. A. Kalabuchova (Zaporozhye State Medical University, 2015)
Aim. Detection of chromosomal aberrations in patients during spontaneous abortion. Methods and results. Cytogenetic study of chorionic samples of the abortions on first trimester of pregnancy. According to the study, the karyotype anomalies were the cause of cardiac embryonic development in 59% of cases. Conclusion. Due to numerous cytogenetic researches of abortion material, anomalies of karyotype are the leading reason of embryonic destruction. The present paper summarizes results of cytogenetic study of the chorionic samples of 26 arrested pregnancies. Frequency and spectrum of karyotype pathology and its correlation with maternal age and term of gestation, sex ratio and type of aberration have been analyzed. The results are compared and discussed with other studies. Most anomalies of karyotype have been conditioned by sporadic genome mutations arising up at ripening of gametes, at an impregnation or in the period of crushing.